Modification of Hydrophobic Polymer-Based Membranes with Gambir Tannin as a Natural Additive to Reduce Humic Acid in Water - Ilham Perkasa Bako (Journal of Chemical Natural Resources, 2025)
Membrane technology is widely used in water treatment processes. This study aims to evaluate the effect of gambir tannin, a natural additive, on the performance of hydrophobic polymer membranes made from polyvinylidene fluoride (PVDF) and polyethersulfone (PES). Membranes were fabricated using the casting–phase inversion method with 0% and 1% tannin concentrations. Membrane characterization included functional group analysis, permeability tests with pure water and humic acid, antifouling performance, and chemical stability. Addition of tannin introduced hydrophilic functional groups into the polymer matrix, resulting in improved membrane porosity, flux recovery ratio (FRR), and fouling resistance. The most significant finding of this study is that the incorporation of 1% gambir tannin increased the pure water flux up to 20.67 L/m²·h for PVDF membranes and 102.46 L/m²·h for PES membranes, while maintaining high antifouling properties and stable performance in acidic and alkaline environments. These results demonstrate the potential of gambir tannin as a sustainable additive for enhancing membrane performance in water purification applications.